Challenges in diagnosing Sarcoidosis in tuberculosis endemic regions: Clinical scenario in India - Guleria, Randeep; Mahashur, Ashok; Ghoshal, Aloke Gopal; Thomas, Prasanna Kumar; Raghu, Ganesh; Baughman, Robert P (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Sarcoidosis is a chronic, systemic disease of unknown etiology that affects multiple organs. The disease was considered rare in developing countries like India. More recently sarcoidosis is being increasingly diagnosed in countries where tuberculosis continues to be endemic. There is a general perception among physicians that the prevalence of sarcoidosis has increased over the last two decades in countries like India. This may be true but could also be related to better awareness of the condition, availability of improved diagnostic facilities and the increased ability of physicians to differentiate it from tuberculosis. In India, diagnosis of tuberculosis is entertained first in patients who may have sarcoidosis and thus, it is very likely for sarcoidosis to be misdiagnosed as tuberculosis, owing to the high prevalence of tuberculosis and clinicoradiological resemblance to the disease. This editorial highlights the challenges in diagnosing tuberculosis in countries where tuberculosis still continues to be endemic.